Geographic mosaics of plant-soil microbe interactions in a global plant invasion - Andonian, Krikor (2012)
Aim Our aim in this study was to document the global biogeographic variation in the effects of soil microbes on the growth of Centaurea solstitialis (yellow starthistle; Asteraceae), a species that has been introduced throughout the world, but has become highly invasive only in some introduced regions. Location To assess biogeographic variation in plant-soil microbe interactions, we collected seeds and soils from native Eurasian C. solstitialis populations and introduced populations in California, Argentina and Chile. Methods To test whether escape from soil-borne natural enemies may contribute to the success of C. solstitialis, we compared the performance of plants using seeds and soils collected from each of the biogeographic regions in greenhouse inoculation/sterilization experiments. Results We found that soil microbes had pervasive negative effects on plants from all regions, but these negative effects were significantly weaker in soils from non-native ranges in Chile and California than in those from the non-native range in Argentina and the native range in Eurasia. Main conclusions The biogeographic differences in negative effects of microbes in this study conformed to the enemy-release hypothesis (ERH) overall, but the strong negative effect of soil biota in Argentina, where C. solstitialis is invasive, and weaker effects in Chile where it is not, indicated that different factors influencing invasion are likely to occur in large scale biogeographic mosaics of interaction strengths.